Ruthenium‐Catalyzed Direct CH Amidation of Arenes Including Weakly Coordinating Aromatic Ketones. Issue 23 (24th April 2013) - Kim, Jiyu; Kim, Jinwoo; Chang, Sukbok
<x xml:space="preserve">Abstract</x> CH activation: The ruthenium‐catalyzed direct sp2 CH amidation of arenes by using sulfonyl azides as the amino source is presented (see scheme). A wide range of substrates were readily amidated including arenes bearing weakly coordinating groups. Synthetic utility of the thus obtained products was demonstrated in the preparation of biologically active heterocycles.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>